The Effect of Compensation, Work Stress, and Development Career Towards Employee Loyalty at PT Bank DKI - Zaky, Achmad; Kusnadi, Kusnadi (Dinasti Publisher, 2024)
The purpose of this study is to analyze the influence of compensation, stress work and career development towards employee loyalty at PT Bank DKI South Pintu Besar Branch Office. The research method used is non-probability sampling. Population from This research is about employees of PT Bank DKI, South Pintu Besar Branch Office a number of 51 person with technique taking sample that is sampling fed up so that the sample consisted of 51 employees. The results of the study showed Compensation has a positive and significant effect on employee loyalty at PT Bank DKI Office Branch Door Big South. Whereas stress Work And Career development does not affect employee loyalty at PT Bank DKI Office South Pintu Besar Branch. With the multiple linear regression equation as follows: Y = 15,953 + 0.687 X 1 - 0.066 X 2 + 0.112 X 3 Recommendation: Upgrade compensation so that loyalty employees at PT Bank DKI Office South Great Door Branch increases